If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x+6x+9=-3x+1
We simplify the equation to the form, which is simple to understand
x+6x+9=-3x+1
We move all terms containing x to the left and all other terms to the right.
+1x+6x+3x=+1-9
We simplify left and right side of the equation.
+10x=-8
We divide both sides of the equation by 10 to get x.
x=-0.8
| 7(7+6)=x(x+4) | | 180=y+(5x+20) | | -12-15x=33 | | 6(v-9)=-2v-14 | | 9(3n-3)=(4n+8)+2 | | 0.3x+3=-2.3x+0.4 | | 7(x-1)+3(3-x)=5(1-x)-3(2x+1) | | 2(90-x)-6=124 | | 961=400+2x | | 15+5(x-10)=3(x-1) | | 16x+16=16x-16 | | 13t-52+8t=21t+28-10 | | 5(z+1)=z+8 | | 5+-6= | | 180=y+5x+20 | | 12x+4=1(x+12) | | -8x-12=36 | | -11+-9= | | 5x+2(x+7)=6x+14 | | -8z-18=-10 | | 11/27=4/9-2x/3 | | 12x+4x^2+9=0 | | -6+18= | | (2x-3)(x+8)=(x-6)(x+4) | | 5t-12=2t+3 | | 1/5(10a-15)=3-2a | | 5x+20=7x-20 | | 125-7x=11x+25 | | 3x^2-41=-4x^2-7x-24 | | 8+6z-5=9z+4-2z | | 9x-8x+3=11 | | 14=12x-2x |